From Policy to Practice: How English Teachers Bridge the Gap in the Classroom - Isnaeni, Laely; Suwartono, Tono; Septika Dewi, Intan Ayu; Rininggayuh, Enggal (International Journal of Research in Education, 2024)
This article explores teachers' implementation of the English Language Policy in Indonesian schools, as it has changed significantly in the last decade. We conducted this study in four public schools in the town of Banjarnegara and one private school in the town of Wonosobo, Central Java Province, Indonesia. In this study, we employed a descriptive-qualitative method. The data were obtained through interviews.  The study addresses three research questions, i.e. how is the school policy on English Language Teaching; how is the teachers’ planning on English Language Teaching; and how do the English teachers implement the policy and planning in their teaching. One school principal and five EFL teachers were interviewed for this purpose. The findings indicate that teachers’ attitudes towards English as a foreign language are influenced by their beliefs and government policy. Moreover, teachers use the curriculum to plan methodically, receive direction, and enhance their expertise. The Merdeka Curriculum allows teachers to use differentiated instructions and various approaches in learning activities, focusing on essential materials and creating a meaningful environment.